Rhinovirus Activates Interleukin-8 Expression via a Src/p110β Phosphatidylinositol 3-Kinase/Akt Pathway in Human Airway Epithelial Cells - Bentley, J. Kelley (American Society for Microbiology, 2007)
Rhinovirus (RV) is responsible for the majority of common colds and triggers exacerbations of asthma and chronic obstructive lung disease. We have shown that RV serotype 39 (RV39) infection activates phosphatidylinositol 3 (PI 3)-kinase and the serine threonine kinase Akt minutes after infection and that the activation of PI 3-kinase and Akt is required for maximal interleukin-8 (IL-8) expression. Here, we further examine the contributions of Src and PI 3-kinase activation to RV-induced Akt activation and IL-8 expression. Confocal fluorescent microscopy of 16HBE14o− human bronchial epithelial cells showed rapid (10-min) colocalization of RV39 with Src, p85α PI 3-kinase, p110β PI 3-kinase, Akt and Cit-Akt-PH, a fluorescent Akt pleckstrin homology domain which binds PI(3,4,5)P(3). The chemical Src inhibitor PP2 {4-amino-5-(4-chlorophenyl)-7-(t-butyl)pyrazolo [3,4-d]pyrimidine} and the PI 3-kinase inhibitor LY294002 each inhibited Akt phosphorylation and the colocalization of RV39 with Akt. Digoxigenin-tagged RV coprecipitated with a Crosstide kinase likely to be Akt, and inhibition of Src blocked kinase activity. Digoxigenin-tagged RV39 colocalized with the lipid raft marker ceramide. In 16HBE14o− and primary mucociliary differentiated human bronchial epithelial cells, inhibition of Src kinase activity with the Src family chemical inhibitor PP2, dominant-negative Src (K297R), and Src small interfering RNA (siRNA) each inhibited RV39-induced IL-8 expression. siRNA against p110β PI 3-kinase also inhibited IL-8 expression. These data demonstrate that, in the context of RV infection, Src and p110β PI 3-kinase are upstream activators of Akt and the IL-8 promoter and that RV colocalizes with Src, PI 3-kinase, and Akt in lipid rafts.